(3eHGOF Yde GdGLJeGY h GdeLJeY GdQjaj (B/s - (3GdaGFOj, eMLhH YWjIs ((3djHjG (B:s (3efThQGJ LGeYI YeQ GdeNJGQ ,s, 1992)
(3jJfGhd GdcJGH eHGOF Yde GdGLJeGY GdYGe eY GdJQcjR Ydi HYV GdUWdMGf GdGSGSjI dgPG GdYGe ceG jfGbT XGgQI GdJZjQ GdGLJeGYj aj GdOhd GdfGejI ef GdGbWGQ GdYQHjIs
(3HHdjhZQGajG (B: (3U(B.306-309s
Keywords: (3GdCSQI h GdeLJeYs; (3GdQjas; (3Yde GdELJeGYs